Measurements of Ice Nucleating Particles in Beijing, China. Issue 14 (30th July 2019) - Bi, K.; McMeeking, G. R.; Ding, D. P.; Levin, E. J. T.; DeMott, P. J.; Zhao, D. L.; Wang, F.; Liu, Q.; Tian, P.; Ma, X. C.; Chen, Y. B.; Huang, M. Y.; et al.
Abstract: Heterogeneous ice nucleating particle (INP) concentrations are reported for a site on the eastern margin of Beijing, China, during the period 4 May to 4 June 2018. INP concentrations were measured continuously at −20, −25, and −30 °C in a repeating cycle by a newly developed, automated continuous flow diffusion chamber, and reached concentrations as high as 2800 sL −1 during dust‐impacted periods. Study average concentrations were 70 ± 70, 230 ± 290, and 430 ± 500 sL −1 at −20, −25, and −30 °C. There was no clear relationship between pollution periods, identified based on fine‐mode particle concentration increases, and INP concentrations or characteristics. Other anthropogenic emissions, such as non‐combustion industrial or agricultural activities play an unresolved role. Plain Language Summary: High concentrations of particles occur over China from varied sources, but we know very little about how they affect clouds. We measured particles in the outside air that can freeze water droplets in clouds, which is important in determining how clouds affect climate and when and where they produce rain and snow. These measurements were made nearly autonomously and continuously, over a month, with a newly modified instrument, which exposes particles to cold cloud conditions to determine the proportion that freeze. The concentrations of freezing nuclei measured in Beijing, China in spring are at the highest end of values reported. Key Points: We report the first continuous flow diffusion chamber measurements of ice nucleating particle concentrations in Beijing, China, for a 1‐month period Ice nucleating particle concentrations were strongly impacted by desert dust transport and had a mixed response to submicron particle concentrations Ice nucleating particle concentrations at −30 °C reached 2, 800 L −1 during a dust‐impacted period